“Efficacy of Kutaki in the Management of Dyslipidemia-A Randomized Control Trial” - WAJPEYI, SADHANA MISAR; KUCHEWAR, VAISHALI (International Journal of Psychosocial Rehabilitation, 2020)
Dyslipidemia is the disorder of lipoprotein metabolism manifested by elevation of the total cholesterol, the low density lipoprotein (LDL) cholesterol and the triglyceride concentrations and a decrease in the high density lipoprotein (HDL) cholesterol concentration in the blood. In Ayurveda, direct reference of Dyslipidemia is not found but it can be correlated with Medodushti and can be included under Santarpanjanya Vyadhi as “Medoroga”. Agni is responsible for all metabolic processes in the body. Decreased Agni leads to “Ama” (undigested/partially digested food) production, which is the main cause of all diseases. To study the efficacy of Kutaki in the management of Dyslipidemia and to compare the effects of Kutaki and Atorvastatin on BMI, serum lipid levels, AST, ALT, serum creatinine and serum urea. In this study,160 patients will be divided randomly into 2 groups (80 in each ).In Group A (Experimental) – Kutaki vati 500 mg will be administered twice a day with water before meal for 60 days and Group B (Control) – Atorvastatin10 mg will be administered at bed time for 60 days.Assessement will be recorded on 0 and 60th day. Changes will be observed in objective outcomes. Kutaki vati will be more effective than Tab. Atorvastatin.